2020
DOI: 10.1177/2325967120935001
|View full text |Cite
|
Sign up to set email alerts
|

Superior Labral Injuries in Elite Gymnasts: Symptoms, Pathology, and Outcomes After Surgical Repair

Abstract: Background: Superior labral anterior-posterior (SLAP) lesions are common among elite gymnasts and throwing athletes. Although SLAP lesions in throwers are well-described in the literature, no study has described the characteristics of SLAP lesions in gymnasts. We aimed to reveal the characteristics of SLAP lesions in gymnasts by comparing the location and extension of these lesions between gymnasts and throwers. Hypothesis: The location and arc of SLAP lesions in gymnasts will be different from those in throwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Caraffa et al [23] reported that the traction force to the intraarticular structure reaches the maximum level during the rings event. Moreover, a paper by Takeuchi et al [10] proposed how, in gymnasts, the traction force to the LHB during suspension events (i.e., hanging from rings or bars) can exert pressure on the superior labrum through the LHB and could potentially result in the formation of a SLAP lesion that extends both anteriorly and posteriorly. This unique injury mechanism, distinct from that seen in throwing athletes, might explain why gymnasts tend to experience SLAP lesions primarily in the anterior part of their shoulders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caraffa et al [23] reported that the traction force to the intraarticular structure reaches the maximum level during the rings event. Moreover, a paper by Takeuchi et al [10] proposed how, in gymnasts, the traction force to the LHB during suspension events (i.e., hanging from rings or bars) can exert pressure on the superior labrum through the LHB and could potentially result in the formation of a SLAP lesion that extends both anteriorly and posteriorly. This unique injury mechanism, distinct from that seen in throwing athletes, might explain why gymnasts tend to experience SLAP lesions primarily in the anterior part of their shoulders.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, a deep partial supraspinatus tear can be present alone or combined with an anteroinferior labral tear (in the case of shoulder instability) or with a posterosuperior labral tear (in the case of posterosuperior glenoid impingement) [8,9]. SLAP lesions occur at a high frequency in gymnastics, and even though they are well described in overhead throwing athletes, they are less studied in gymnasts and seem to have a different arc of lesion [10,11]. Moreover, even though dislocation and subluxation are commonly observed injuries, both in training and competition, it is important to underline that in gymnasts, inferior subluxation can be considered physiologic since it is necessary for the athlete to perform some of the routines and as such, it is considered part of the training and shall not be overcorrected [9].…”
Section: Introductionmentioning
confidence: 99%
“…While gymnasts are often grouped with overhead athletes, independent evaluation should be considered because of the unique needs of the gymnast's shoulder compared with other overhead athletes. 32 Further evaluation of PROs in gymnasts could provide essential insights that would improve treatments and recovery after SLAP tears.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,19,22,27,31 Gymnastics is a sport commonly associated with superior labral anterior-posterior (SLAP) tears, with pathologies presenting similarly to those of overhead athletes. 4,9,12,14,32 Historically, operative treatment of SLAP pathologies in young patients consisted of labral and biceps anchor repair. Outcomes were unsatisfactory, with variable § postoperative satisfaction and functional outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation